Lactic acid regulates antitumor immunity in canine invasive urothelial carcinoma - Taiki Kato; Nao Okauchi; Tomoki Motegi; Masashi Sakurai; Shingo Maeda; Daiki Kato; Takayuki Nakagawa; Kazuyuki Uchida; Takuya Mizuno; Masaya Igase (PLoS ONE, 2025)
Canine invasive urothelial carcinoma (iUC) is a fatal malignant neoplasm that closely resembles human muscle-invasive bladder cancer in terms of histopathological features, molecular alterations, and clinical behavior. These similarities suggest that canine iUC represents a valuable spontaneous model for studying human bladder cancer. Tumor microenvironment (TME) plays a crucial role in tumor progression. Tumor-derived lactic acid has been implicated in the suppression of antitumor immunity and the promotion of tumor growth by altering the metabolic status of immune cells within the TME. However, the interaction between tumor metabolism and immune cells in the TME remains unclear in dogs. This study reanalyzed previously reported RNA-seq data to investigate the mechanisms underlying enhanced glycolysis in canine iUC. ERBB2 overexpression was found to induce AKT phosphorylation and increase extracellular lactic acid levels in vitro, activating the ERBB2-AKT-glycolysis axis and upregulating monocarboxylate transporter 4 (MCT4). MCT4 knockdown by RNA interference or pharmacological inhibition with diclofenac reduced lactic acid levels in the culture supernatant. Furthermore, MCT4 expression in canine iUC tissues was positively correlated with infiltrating regulatory T cell (Treg) counts. Functional studies revealed that lactic acid promoted Treg differentiation and suppressed IFN-γ production by effector T cells. These findings indicate that MCT4 mediates lactic acid efflux from glycolytic tumor cells, contributing to the suppression of antitumor immunity. Targeting tumor metabolism through MCT4 inhibition may represent a promising therapeutic strategy for canine iUC. Therefore, insights from the metabolic and immunological landscape of canine iUC may inform the development of translational therapies for both veterinary and human oncology.